Cultivating a "Cosmic Perspective" in Theology: Reading William R. Stoeger with Laudato Si' - Schutz, Paul J. (Theological studies, 2019)
The anthropocentric orientation and treatments of evolution and ecology found in Laudato Si' undermine its potential for operationalizing its vision of "splendid universal communion." Jesuit astronomer William Stoeger's conceptions of experience and knowledge provide a resource for addressing these concerns and for fostering a perceptual turn to the cosmos in theology. Comparisons with Lonergan and Rahner illustrate the potential of Stoeger's approach, and the Spiritual Exercises illustrate his vision. The article concludes by considering the theological horizons of his approach.